The Analysis of Students’ English Competence in the Grammar Section in the Paper-Based TOEFL: A Case Study at English Department in Bunda Mulia University - Jonathan Tanihardjo (Journal of English Language and Culture, 2017)
TOEFL is a standardized test used to measure non-native English speakers’ proficiency. Even though the paper-based test (PBT) as well as the computer-based test (CBT) may seem obsolete and have progressively been replaced by the Internet-based Test (iBT), most universities and institutions still make use of PBT as a graduation requirement. There are three sections in PBT, namely listening comprehension, structure / written expression and reading comprehension. However, this study only aims to provide information on students’ problems, particularly those in the grammar section in the PBT TOEFL. The study involved students of the Culture and English Department in Bunda Mulia University from semester 6 who are already finished with the whole grammar subjects: Grammar I – IV and whose scores in the structure / written expression section are below 50 in the pre-test. Two Random paper-based tests are opted for in the post-test, and therefore there are 80 questions in total. The purposes of this research are to find out (1) the most frequent types of questions to occur and (2) the mistakes students tend to make. The study is then expected to help both lecturers and students to have a clearer picture of types of questions in the PBT TOEFL structure / written expression and know how to overcome problems. Keywords: PBT TOEFL, structure / written expression, mistakes